WAWASAN AL-QUR'AN TENTANG EKOLOGI: (Kajian Tematik Ayat-ayat Konservasi Lingkungan) - Eko Zulfikar (QOF, 2018)
As hudan li al-na>s, The Qur’an is certainly not only a metaphysical-eschatological sense, but also concerns to the practical problems of human life in the world, includes the basic guidelines on how humans take care of the universe and conserve the environment. This paper introduced some ways or humans efforts in conserving the environment. This study  focused on the searching of verses on ecology, and it also  examined verses relating to environmental conservation in the Qur’an by using thematic method. It was found that the verses about the ecology introduced by the Qur'an were in the form of an environment (al-bi>ah), the whole world (al-‘a>lami>n), the sky or universe (al-sama>’), earth (al-ard}), human (al-insa>n), fauna (al-an’a>m or da>bbah), flora (al-naba>t or al-h{arts), water (ma>’), angin (al-ri>h}), sun (al -syams), moon (al-qamar), star (al-buru>j), and mountain (jabal). In seeking to identify the use of the existence of the verses about ecology, there are at least five efforts to conserve the environment: (1) maintain environmental cleanliness, (2) maintain the balance of nature, (3) plant trees for reforestation, (4) manage the land dead and empty, and (5) maintain and protect animals.